Jordanian stereotypes of Americans: A study at Yarmouk University in Irbid, Jordan - Gibson , Irene; Banihani, Mohammed Saleh; Gibson, Peter Joseph (Journal of Interdisciplinary Studies in Education, 2017)
This study investigates Jordanian student perceptions of Americans through a survey of Yarmouk University in Irbid, Jordan. Specifically, this study identifies pervading stereotypes held about Americans, and where these stereotypes were learned. Data was collected June through August of 2014 from Yarmouk University students through a distribution of surveys. Students reported learning the most about Americans through films (22%). For a majority of students, the response for a trait related to Americans had a significant association with the response for the same trait related to Jordanians. Traits commonly and significantly associated with Americans were lack of family values, women being promiscuous, wanting to invade other countries, and disliking Muslims. The trait commonly and significantly associated with Jordanians was being generous.